European studies in Asia : contours of a discipline - Georg Wiessala (Routledge contemporary Asia series, 2014)
"As countries across Asia continue to rise and become more assertive global powers, the role that Higher Education has played, and continues to play in this process is an issue of growing pertinence. Furthermore, understanding the relationship between Europe and Asia fostered by historical and contemporary knowledge transfer, including Higher Education, is crucial to analysing and encouraging the progress of both regional integration and inter-regional cooperation.With a specific focus on international Higher Education, European Studies in Asia investigates knowledge transfer and channels of learning between Europe and Asia from historical, contemporary, and teaching perspectives. The book examines a selection of significant historical precedents of intellectual dialogue between the two regions, and in turn, explores contemporary cross-regional discourses both inside and outside of the official frameworks of the European Union (EU) and the Asia-Europe Meetings (ASEM). Drawing on extensive case-studies based on many of his own teaching experiences, Georg Wiessala addresses key questions, such as the nature and construction of the European Studies in Asia curriculum; aspects of 'values', co-constructed learning and adult pedagogy in the discipline of European Studies in Asia; the politics of Asian host cultures, the 'internationalization' of Asian Higher Education and the experiences and expectations of tertiary sector students of this subject in Asia, Australia and New Zealand. In doing so, the author articulates a range of outcomes for the further development of Higher Education co-operation agendas between Asia and Europe, in the discipline of European Studies, and in related fields such as International Relations. This case-study led book makes an original and novel contribution to our understanding of European Studies in Asia. As such, it will be of great interest to students and scholars of Asian Education, Comparative Education, European Studies and International Relations. "--